Telomere- and Telomerase-Associated Proteins and Their Functions in the Plant Cell - Procházková Schrumpfová, Petra; Schořová, Šárka; Fajkus, Jiří (Frontiers in Plant Science, 2016)
Telomeres, as physical ends of linear chromosomes, are targets of a number of specific proteins, including primarily telomerase reverse transcriptase. Access of proteins to the telomere may be affected by a number of diverse factors, e.g., protein interaction partners, local DNA or chromatin structures, subcellular localization/trafficking, or simply protein modification. Knowledge of composition of the functional nucleoprotein complex of plant telomeres is only fragmentary. Moreover, the plant telomeric repeat binding proteins that were characterized recently appear to also be involved in non-telomeric processes, e.g., ribosome biogenesis. This interesting finding was not totally unexpected since non-telomeric functions of yeast or animal telomeric proteins, as well as of telomerase subunits, have been reported for almost a decade. Here we summarize known facts about the architecture of plant telomeres and compare them with the well-described composition of telomeres in other organisms.